PENERAPAN STRATEGI PEMBELAJARAN AKTIF BINGO REVIEW UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON KELAS X SMA NEGERI 1 KAMPAR TIMUR - Nanik Muslihatun Nisa; R. Usman Rery; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The application of active learning strategy bingo review to improved the students achievement on the subject of hydrocarbon in class X SMAN 1 Kampar Timur has been done. The research was a experiment with pretest-posttest design. The population consisted of four classes grade. The sample were two classes, where class X9 as an experimental class and the class X10 as an control class, they selected after normality and homogeneity test. Experimental class applied to active learning strategy bingo review and the control class was not. Technique data analysis used the t-test and gain normalized test. Based on data analysis obtained tcount > ttable (1,81>1,66), means that application of active learning strategy bingo review improved student learning achievement on the topic of hydrocarbon in class X SMAN 1 Kampar Timur. Improved of student achievement at experiment class categored high with N-gain normalized is 0,70 and the in control class categored medium with N-gain normalized is 0,61.Key words: Active Learning Bingo review Strategy, Learning Achievement, Hydrocarbons